'Childhood is measured out by sounds and sights and smells, before the dark of reason grows': children's geographies at 12. Issue 6 (1st November 2016) - Philo, Chris
Abstract : This Keynote essay argues for a supplement to existing studies in children's geographies, one that explores the potential of a non -child-centric children's geography alert to the work done by the figure of 'the child' in all manner of worldly situations. Taking a cue from the poetry of John Betjeman, notably his1960 Summoned by Bells, the essay considers both the intimate spaces of childhood – ones gauged by the immediacies of 'sounds and sights and smells' – and the challenges posed by a wider world raddled by adult preoccupations and abuses, those characterised by Betjeman as stemming from 'the dark of reason'. The essay builds from this foundation to address the 'darkness' in two sets of Nazi children's wartime geographies, as well as engaging with the complexities of Theodor Adorno and Max Horkheimer's claims, in the horizon of WWII, about the 'dialectic of enlightenment'. Within the latter – and also, notably, in Adorno's later writing – the figure of 'the child' surfaces as one miniscule crumb of hope, of experiencing and knowing the world otherwise, set against the face of adult Enlightenment's seemingly inevitable decay. At the close, Adorno's own brief dalliance with imagining a small slice of children's geographies allows the essay to arc back towards its original claims, and to a renewed sense of why childhood 'sounds and sights and smells' continue to matter far beyond just the domain of geographers researching children.